Pengaruh Motivasi Kerja Dan Disiplin Terhadap Kinerja Karyawan Koperasi Kasih Indonesia Cilincing Jakarta Utara - Asep Rifaldi Agustian; Eko Sudarso (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstrak. This research was conducted at the Kasih Indonesia Cooperative in Cilincing, North Jakarta, which aims to determine the effect of Motivation and Work Discipline on Employee Performance at the Kasih Indonesia Cooperative in Cilincing, North Jakarta, both partially and simultaneously. The method used is saturated sampling using a sample of 60 employees. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation tests, determination coefficient analysis and hypothesis tests (T and F). The results of this study are that Motivation has a positive and significant effect on Employee Performance. This is based on the results of the regression test obtained by the regression equation Y = 16.493 + 0.610 X1 and the results of the hypothesis test obtained with a Tcount value > Ttable or (7.762 > 2.002), this is strengthened by a probability significance of 0.00 <0.05, thus H0 is rejected and H1 is accepted, meaning there is a partial significant effect between motivation on employee performance at the Kasih Indonesia Cooperative in Cilincing, North Jakarta. Work Discipline has a positive and significant effect on employee performance. This is based on the results of the regression test obtained the regression equation Y = 15.818 + 0.587 X2 and the results of the hypothesis test obtained with a value of Thitung> Ttabel (6.803> 2.002), this is strengthened by a probability significance of 0.00 <0.05, thus H0 is rejected and H2 is accepted meaning there is a significant partial influence between work discipline on employee performance at the Kasih Indonesia Cooperative Cilincing North Jakarta. Motivation and Work Discipline have a positive and significant effect on employee performance. This is based on the results of the regression test Y = 8.268 + 0.433X1 + 0.362X2 and the results of the hypothesis test obtained with a value of Fhitung> Ftabel or (49.663> 2.770), this is also strengthened by a ρ value <Sig 0.050 or (0.00 <0.05). Thus H0 is rejected and H3 is accepted. This means that there is a significant simultaneous influence between motivation and work discipline on employee performance at the Kasih Indonesia Cooperative in Cilincing, North Jakarta.